Sustainable self-compacting mortars: mechanical, durability and microstructural evaluation with cement replacement materials under aggressive environmental conditions - Karabulut, Büşra; Yön, Merve Şahin; Karataş, Mehmet (Taylor & Francis Ltd, 2026)
The aim of this study is to assess the mechanical, physical and durability properties of environmentally friendly self-compacting mortars produced using materials containing industrial waste and natural stone. The test series were produced by substituting diatomite (D) and C class fly ash (F) with Portland cement (PC) up to 30% by weight. To evaluate the workability, mechanical and durability properties of self-compacting mortars (SCM), a total of 19 series, one of which was a reference sample, were prepared. The samples, whose mechanical properties and durability properties were investigated under sulphate attack and freeze-thaw effects, were prepared as 40 & times; 40 & times; 160 mm, and the series, whose physical properties were examined, were prepared as 50 & times; 50 & times; 50 mm. Also, SEM/EDS (Scanning Electron Microscope - Energy Dispersive X-Ray) and XRD (X-Ray Diffraction) analyses were carried out to evaluate the microstructural properties of the mixtures. When the 90-day compressive strength results were examined, it was determined that the highest decrease in compressive strength compared to the control sample occurred in the D20F10 sample with a rate of 61%, and the least decrease occurred in the D5 series with a rate of 10%. When the losses in compressive strength were evaluated after 50 freeze-thaw cycles, it was determined that there was a 100% reduction in the binary and ternary series containing D15 and D20. After six months of sulphate exposure, the D5F25 sample exhibited the most significant compressive strength reduction at roughly 40%, whereas the D15F15 series experienced the least compressive strength decline at around 5%.
Keywords: Diatomite; fly ash; freeze-thaw effects; self-compacting mortars; sulphate attack